(untitled) (MMIT Proceedings, 2025)
Today, the success of the economy, particularly in entrepreneurship, depends on the highly developed and effective use of information technologies. Over the past five years, the internet commerce market has experienced significant growth, affecting all trends in the local economy. This paper investigates the current state of the local e-commerce industry, with a particular focus on technologies, platforms, payment methods, and market strategies. Additionally, it provides a futuristic perspective on the digital economy by exploring the strategies and trends shaping the current e-commerce industry.